Anisotropic thermal and electrical transport of Weyl semimetal TaAs. (9th November 2017) - Xiang, Junsen; Hu, Sile; Lv, Meng; Zhang, Jiahao; Zhao, Hengcan; Chen, Genfu; Li, Wei; Chen, Ziyu; Sun, Peijie
Abstract: We report on anisotropic electrical, thermal as well as thermoelectric properties of the prototypical Weyl semimetal TaAs. Compared to the normal metallic behavior along a axis, TaAs is more electrically resistive along c axis and exhibits a semiconductor-like resistivity upturn below T ≈ 25 K. In the same temperature range, the thermal conductivity along c axis shows a pronounced maximum of 183 W K m − 1 characteristic of a crystalline solid, three times higher than that of a axis. The thermoelectric power, while exhibiting enhanced values around room temperature, becomes diminished in a substantial range of temperature ( T < 50 K) for both axes. Together with the enhanced Nernst signals, this hints at a dominating ambipolar diffusion as is frequently seen in a compensated semimetal. An in-depth investigation of the anisotropic transport quantities is expected to yield deep insights into the propagating Weyl fermions in TaAs.